PSYCHOLOGY OF FOOD SECURITY: STRATEGIES TO OVERCOME FOOD INSECURITY AND ITS IMPACT ON MENTAL HEALTH - Hafifah, Nur; Karim, Abdul (Jurnal At-Taujih, 2025)
Unstable food security can cause serious psychological impacts such as anxiety and stress, which affect people's mental health. This study aims to examine how food security affects individuals' psychological conditions and coping strategies used in dealing with food uncertainty. A qualitative research method with a phenomenological approach was used, involving in-depth interviews, observation, and documentation of participants experiencing food uncertainty. The results showed that food uncertainty triggers anxiety and stress, but individuals develop adaptive coping strategies such as food diversification and social support to reduce psychological stress. In addition, the use of an interactive approach in education has been shown to be effective in reducing anxiety and increasing motivation. These findings emphasize the importance of integrating psychological aspects in food security programs to improve the mental and physical well-being of the community as a whole.